2008
DOI: 10.1080/02841850802409539
|View full text |Cite
|
Sign up to set email alerts
|

Crohn's disease evaluated with magnetic resonance enteroclysis: diagnostic performance of experienced and inexperienced readers before and after training

Abstract: Before training, most findings of Crohn's disease in the terminal ileum were evaluated with high diagnostic performance by all readers. However, the inexperienced readers evaluated BWU with a low sensitivity and overestimated the number of FIS, number of ABS, and increased BWT in the jejunum. After training, evaluation by inexperienced readers of BWU and increased BWT in the jejunum improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…In conclusion aiming the assessment of interobserver variability is beyond the scope of our research. We affirm that MRE is a supplementary technique rather than a main diagnostic and scoring tool due to our finding which is MRE underestimates CD activation scores and due to the findings of other studies (1)(2)(3)(4) declaring that it has inter-and intra-observer variability.…”
Section: Mr Enterography: Still Complementary To Ses-cd For Evaluatiosupporting
confidence: 54%
See 1 more Smart Citation
“…In conclusion aiming the assessment of interobserver variability is beyond the scope of our research. We affirm that MRE is a supplementary technique rather than a main diagnostic and scoring tool due to our finding which is MRE underestimates CD activation scores and due to the findings of other studies (1)(2)(3)(4) declaring that it has inter-and intra-observer variability.…”
Section: Mr Enterography: Still Complementary To Ses-cd For Evaluatiosupporting
confidence: 54%
“…The main limitation in the reports is the distinct interobserver variability for many of these MRI features. Additionally, the interobserver reproducibility of MRI features in CD must be optimal when used by different observers in different centers to be clinically useful (4). The validation and standardization of MRI scoring systems need optimal interobserver variability and reproducibility values.…”
Section: Mr Enterography: Still Complementary To Ses-cd For Evaluatiomentioning
confidence: 99%
“…Also, the radiologists involved in this study have an established profile in small bowel imaging, a factor that has been shown to be relevant for more accurate diagnosis of small bowel MRI. 35 The third and fourth points of heterogeneity in CD are that the disease manifestations in any particular segment vary in severity and chronicity. Abscesses, fistula, and sinus formations are known complications of intestinal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have evaluated the interobserver agreement in MRE and CTE (or MR and CT enteroclysis) in patients with known or suspected CD and found moderate to excellent agreement for the diagnosis and specific findings related to CD. 10,14,[20][21][22][23][24][25][26][27] Two recent studies compared the diagnostic accuracy and interobserver agreement in MRE and CTE. Lee et al 10 found equally high diagnostic accuracies, and substantial to excellent agreement for detection of CD in the upper and lower small bowel.…”
Section: Discussionmentioning
confidence: 99%